A novel flow and pressure catheter for complete interventional cardiology physiology management. (14th October 2021) - Sette, M M
Abstract:  : Ischemia with No Obstructive Coronary Artery (INOCA) in angina patients increases the risk of major cardiac events, with a 1.5x increased mortality rate. There is a link between COVID-19 infection and impairment in the myocardial micro-vasculation which may cause an increase of INOCA patients. Fractional Flow Reserve (FFR), is the standard of care in cardiology but its diagnostic function is only related to Obstructive Coronary Artery disease (or epicardial) and it is ineffective with INOCA. The lack of effective and accurate tools for timely evaluation of coronary impairments creates a clinical unmet need. The PhysioCath catheter was developed within the Eurostars project "FP-Catheter, E!113577" aims to resolve this need a provide an effective tool to interventional cardiologists. The main project outcome is a catheter prototype equipped with a blood flow velocity sensor based on a thermo-convection principle, and a fiber optic pressure sensor (based on Fabry-Perot principle). While the use of Fabry-Perot type of sensor is already standard in the industry, the use of a thermo-convection sensor represents a progress with respect the state of the art. The sensor creates an overheat of 7°C above the physiological blood's temperature (considered as being within the safety limits), and it exchanges thermal power with the blood stream. The power is then measured and converted to velocity by means of a calibration curve. The project encompassed interviews with 14 clinical experts, the summary of the interviews indicated that the preferred form of the device is an over the wire microcatheter, with rapid exchange. Within the project then, it was developed a 3Fr microcatheter, with a rapid exchange section of 24cm. Both pressure sensor and flow velocity sensor were integrated in this embodiment. Finally, the PhysioCath prototype was evaluated in a bench test study. The test setup was composed by an anatomical silicone phantom of the aortic root and the coronaries (Elastrat, Geneva, Switzerland), perfused with a peristaltic pump (Harvard Apparatus, Holliston MA, US). The measurements performed by the flow velocity sensor were compared against and external doppler flow velocity sensor. While the pressure measurement was assessed for stability and presence of drift. The data processing revealed and extreme accuracy in the measurement of flow based indexes like CFR (±6% variability), accuracy of the blood flow velocity measurement (±10%), and extreme stability in the measurement of both pressure and flow velocity. In the second part of the project (that is currently ongoing), it will be studied the performance of the device within an animal setting. In conclusion, the PhysioCath device is a microcatheter integrating bot pressure measurement and blood flow velocity measurement. Its performance is of very high accuracy and stability, that represent a main step ahead with respect the current state of the art, based mainly on thermodilution. Funding Acknowledgement: Type of funding sources: Public grant(s) – EU funding. Main funding source(s): Eureka-Eurostars